Cellulose-assisted electrodeposition of zinc for morphological control in battery metal recycling. Issue 13 (4th May 2022) - Hoogendoorn, B. W.; Parra, M.; Capezza, A. J.; Li, Y.; Forsberg, K.; Xiao, X.; Olsson, R. T.
Abstract : This study demonstrates that nanocellulose can be used in zinc electrodeposition to promote the formation of more suitable deposits for efficient metal recycling. Abstract : Cellulose nanofibers (CNFs) are demonstrated as an effective tool for converting electrodeposits into more easily detachable dendritic deposits useful in recycling zinc ion batteries via electrowinning. The incorporation of CNFs at concentrations ranging from 0.01 to 0.5 g L −1 revealed a progressively increasing and more extensive formation of a nacre-like dendritic zinc structure that did not form in its absence. Increasing the CNF concentrations to 0.5 g L −1 resulted in the most extensive formation of dendritic structures. The explanation for the observed phenomenon is the ability of CNFs to strongly interact with metal ions, i.e., restricting the mobility of the ions towards the electrowinning electrode. At the highest concentration of CNFs (0.5 g L −1 ), in combination with the lowest current density (150 A m −2 ), electrodeposition was limited to the extent that formed deposits were almost non-existent. The electrodeposition in the presence of CNFs was further evaluated at different temperatures of 20, 40 and 60 °C. The dendritic formation was increasingly suppressed with increasing temperatures, and at a temperature of 60 °C, the electrodeposited morphologies could not be differentiated from the morphologies formed in the absence of the cellulose. The results stemmed from a greater mobility of the metal ions at elevated temperatures, while at the same time suggests an inability of the CNF to strongly associate the metal ions at elevated temperatures. High-pressure blasted titanium electrodes were used as a reference material for accurate comparisons, and electron microscopy (FE-SEM) and X-ray diffraction were used to characterize zinc morphologies and crystallite sizes, respectively. This article reports the first investigation on how dispersions of highly crystalline cellulose nanofibers can be used as a renewable and functional additive during the recycling of battery metal ions. The metal-ion/cellulose interactions may also allow for structural control in electrodeposition of other metal ions.